The Use of Satellite Observations in Ice Cover Simulations - Preller, Ruth H.; Walsh, John E.; Maslanik, James A. (1992)
The combination of numerical models and observational data can provide a unique tool for studying the complex interactions of the atmosphere, the ice, and the ocean. The formulation of numerical ice and coupled ice-ocean- atmosphere models is based on our knowledge of dynamic and thermodynamic principles and how they relate to observed ice conditions. Field experiments such as the Arctic Ice Dynamics Experiment (AIDJEX) Pritchard, 1980 and the Marginal Ice Zone Experiment (MIZEX) have provided observational data from which the basis of many of the formulations for ice drift, internal ice stresses, heat exchange, etc., have come. Numerical models, on the other hand, may be used to provide information on ice drift, ice thickness, and ice concentration in regions where observations are scarce or missing. In addition, numerical models may be used to forecast ice conditions. Ice model development, Data analysis and assimilation, Model evaluation.